The Influence of Elemental Sulphur and Phosphorus on the Performance of Faba bean (Vida faba) Grown in Two Alkaline Soils - Elamin, E A; Ibrahim, I S; Musa, Z A (Annals of Arid Zone, 2016)
A factorial completely randomized pot experiment was conducted in two soil types namely: alkaline non-calcareous and calcareous. Representative composite surface (0-30 cm) soil samples were collected from each soil type. The treatments included: sulphur, phosphorus, phosphorus + sulphur and a control. Eight seeds of faba bean (Vicia faba cv. Suleimi variety) were sown early winter in each pot and thinned two weeks later to four pla’nts per pot. Plants were sampled at !lowering and harvesting stages and analysed for dry matter yield, nitrogen, phosphorus, potassium, iron, ’zinc, manganese and copper. The results at the !lowering stage revealed that the differences between the treatments were significant for the dry maller, nitrogen and phosphorus, but not significant for potassium and trace elements except copper in the first season. In the second season the differences were significant for all nutrients with the exception of nitrogen, phosphorus and copper. At harvest the measured parameters were significantly affected by the treatments in both the seasons.